Realization of principles of the Bolonskogo process in ecological formation of future specialists - LUKYANOVA, Larisa (Continuing Professional Education: Theory and Practice, 2019)
In the article the points of view of scientists about expedient approaches of realization of basic principles of the Bolonskogo process in educational space of Ukraine are analysed. Technologies of ecological formation of future specialists taking into account the requirements of Bolonskoy declaration are defi nite. Directions of scientifi c search, cooperant to the rise of effi ciency of ecological education in higher educational establishments of Ukraine, are grounded.